Water-soluble hyaluronic acid–hybridized polyaniline nanoparticles for effectively targeted photothermal therapy1. Issue 18 (14th May 2015) - Jiang, Bang-Ping; Zhang, Li; Zhu, Yang; Shen, Xing-Can; Ji, Shi-Chen; Tan, Xue-You; Cheng, Lei; Liang, Hong
<x xml:space="preserve">Abstract</x> Water-soluble hyaluronic acid–hybridized polyaniline nanoparticles show effective photothermal ablation of cancer with targeted specificity.